The Role of Bank-Affiliated Directors in Monitoring Earnings Management and Improving Financial Reporting Quality: Evidence from Banks Listed on the Iraq Stock Exchange - Gazi Hasan, Majid; Rezazade, Javad; Sepasi, Sahar (Business, Marketing, and Finance Open, 2027)
The primary objective of this study was to examine the monitoring role of bank-affiliated directors (BAFD) in relation to earnings management (EM) and financial reporting quality (FRQ) among banks listed on the Iraq Stock Exchange. To this end, panel data from 15 banks covering the period from 2015 to 2023 were analyzed, yielding 135 bank-year observations. The research hypotheses were tested using panel regression models and the estimated generalized least squares (EGLS) method, incorporating cross-sectional weights and random effects, as appropriate. Diagnostic procedures included panel unit root tests, the Chow F-test, the Hausman test, multicollinearity assessment, and heteroskedasticity tests. The findings indicated that the presence of bank-affiliated directors had a significant negative effect on earnings management, suggesting that a greater representation of such directors reduces earnings manipulation in banks. This variable also had a significant positive effect on financial reporting quality, thereby improving the transparency and reliability of financial information. However, the moderating effects of bank size and free cash flow on the relationship between bank-affiliated directors and earnings management were not supported. Among the control variables, bank size had a negative effect on earnings management, whereas return on assets had a positive effect on financial reporting quality. Overall, the results indicate that the presence of bank-affiliated directors can function as an effective corporate governance mechanism for improving financial reporting quality and constraining opportunistic managerial behavior in emerging markets.